2013
DOI: 10.4103/2278-330x.114145
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reconstruction methods and pathological factors on survival after pancreaticoduodenectomy

Abstract: Background:Surgery remains the mainstay of therapy for pancreatic head (PH) and periampullary carcinoma (PC) and provides the only chance of cure. Improvements of surgical technique, increased surgical experience and advances in anesthesia, intensive care and parenteral nutrition have substantially decreased surgical complications and increased survival. We evaluate the effects of reconstruction type, complications and pathological factors on survival and quality of life.Materials and Methods:This is a prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Binziad S et al, (19) demonstrated that PJ duct-to-mucosa anastomosis was secure, produced minimum pancreatic leak and minimum bleeding in comparison to the other approaches of reconstructions. Sert OZ et al, (20) concluded that preoperative elevated ALP, AST, ALT, GGT values, low haemoglobin levels and soft texture of remnant pancreatic tissues were revealed to be connected with PF that happens post-PD.…”
Section: Discussionmentioning
confidence: 99%
“…Binziad S et al, (19) demonstrated that PJ duct-to-mucosa anastomosis was secure, produced minimum pancreatic leak and minimum bleeding in comparison to the other approaches of reconstructions. Sert OZ et al, (20) concluded that preoperative elevated ALP, AST, ALT, GGT values, low haemoglobin levels and soft texture of remnant pancreatic tissues were revealed to be connected with PF that happens post-PD.…”
Section: Discussionmentioning
confidence: 99%
“…The probability to involve and stratify all potential impact risk factors determining all subgroups in one study are practically impossible. For this reason, there are many reviews collecting and analyzing the data, but the results remain diverse and confusing (13,14,15). Reasonably, until the consensus is reached, every referent institution with high caseload should undertake its own study based on the observations and experience for the eligibility between these 2 techniques, DA (invagination) and DMA.…”
Section: Discussionmentioning
confidence: 99%
“…11 Postoperative pancreatic fistula (POPF) is the major cause of postoperative morbidity and its incidence is 9% to 29%. 12 POPF significantly affects the patient's quality of life and also increases the treatment cost. Hospital stay is prolonged and postoperative mortality is also increased.…”
mentioning
confidence: 99%